Diferentes pruebas diagnósticas para detectar Ehrlichia Canis. - Arroba Vera, Carolina Lisbeth (2022)
This research has been carried out in order to collect information on diagnostic tests that allow Ehrlichia canis to be detected. Ehrlichia canis is the main etiological agent of canine monocytic Ehrlichiosis (CME). This agent is transmitted to dogs by the brown tick (Rhipicephalus sanguineus), which serves as a vector for this disease. As the symptomatology is varied, it is necessary to carry out diagnostic tests that allow Ehrlichia canis to be detected. There are various methods or diagnostic tests. We can classify these tests as direct or indirect diagnostic tests. Direct tests consist of directly observing the etiologic agent in animal samples suspected of having an Ehrlichia canis infection. Of these we have microscopic observation, cultivation and molecular methods. On the other hand, indirect tests aim to determine the presence of the infectious agent by assessing the immune response developed by the host. Among them we have indirect immunofluorescence (IIF) such as Enzyme-linked immunosorbent assay (ELISA) or immunoblot. The different tests applied to the diagnosis of this disease will be analyzed, as well as the advantages and disadvantages that these tests present.